Fuzzy Logic - Volosencu, Constantin (Artificial Intelligence, 2020)
This book promotes new research results in the field of advanced fuzzy logic applications. The book has eight chapters, with the following thematic areas: fuzzy mathematics, adaptive neuro-fuzzy inference system, inference methods, expert systems, electrical systems, and application in management and field-programmable gate array. The introductory chapter aims to recall some algebraic relations that describe fuzzy rule bases and fuzzy blocks as algebraic applications. Other works presented are: a study on the convergence of sequence spaces with respect to intuitionistic fuzzy norms and their topological and algebraic properties; an ANFIS application to identifying the online bearing fault; methods of conditional inference for fuzzy control systems; an application of fuzzy logic and fuzzy expert systems in material synthesis methods; control of electrical systems in conditions of incomplete information regarding the values of diagnostic parameters; a methodology for evaluating the causality of factors in organization management; and a technical study on the functional safety of an FPGA fuzzy logic controller. The authors have published worked examples and case studies resulting from their research in the field. Readers will have access to new solutions and answers to questions related to the emerging field of theoretical fuzzy logic applications and their implementation.